2015
DOI: 10.1186/s12879-016-1407-4
|View full text |Cite
|
Sign up to set email alerts
|

A 20-year retrospective cohort study of TB infection among the Hill-tribe HIV/AIDS populations, Thailand

Abstract: BackgroundA retrospective cohort study was conducted to determine the situation, trend, and factors associated with TB infection, and factors related to the life status among the HIV/AIDS Hill-tribe in Northern Thailand. Hill-tribe people have been migrating to and formed settlements along the Thai border areas for many decades. There are now having 1.6 million people of 6 different groups–Akha, Lahu, Lisu, Hmong, Yao and Keren–each with a specific culture, language and lifestyle. The Hill-tribe becomes a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Some Thai people live in poor economic conditions, have low levels of education and face several barriers to access to medical services, such as language, distance, and stigmatization [ 12 ].. The hill tribe people are a good example of those with atypical access to Thai medical services, since they are living in rural areas and have specific cultures and perceptions, particularly with unrespect to access to medical services, including immunization for children [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some Thai people live in poor economic conditions, have low levels of education and face several barriers to access to medical services, such as language, distance, and stigmatization [ 12 ].. The hill tribe people are a good example of those with atypical access to Thai medical services, since they are living in rural areas and have specific cultures and perceptions, particularly with unrespect to access to medical services, including immunization for children [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that factors such as the country or health setting, economy, process of treatment, internal policy and management are all related to TB treatment outcomes [3][4][5][6]. Additionally, countries that are faced with problems of HIV/AIDS must double their efforts in their management of TB patients, especially in areas that border two or more countries, such as the Thailand-Myanmar-Republic of Laos border communities [7]. Both Thailand and Myanmar have a long border that stretches from the north to the south and is approximately 2,401 km [8].…”
Section: Introductionmentioning
confidence: 99%
“…Between 2010 and 2018, 14,024 TB cases were reported in Chiang Rai province, and 37.5 percent were identified as members of the stateless population, including individuals of Burmese and Laos nationality [17]. A large proportion of TB cases were reported by Thai hospitals along the borders of Thailand-Myanmar and Thailand-Republic of Laos [7]. Mae Sai and Chiang Sean Hospitals were reported to have the greatest proportion of new foreign TB patients in Chiang Rai province.…”
Section: Introductionmentioning
confidence: 99%
“…12 These two tribes have their own culture, and lifestyles including sexual behaviors. 13 Most Hmong and Mien men and women have their first sexual intercourse at young age, and get married at early age as well. 14 Moreover, these tribes have a unique culture of polygamy.…”
Section: Introductionmentioning
confidence: 99%